Grain yield of corn at different population densities and intercropped with forages - Nascimento, Jose M. do; Furlani, Carlos E. A. [UNESP]; Chioderoli, Carlos A.; Queiroz, Renata F. de; Bertonha, Rafael S. [UNESP]; Cavichioli, Fabio A. [UNESP] (Univ Federal Campina Grande, 2015)
The no-tillage system optimizes agricultural areas, maintaining the supply of straw and promoting crop rotation and soil conservation. The aim of the present study was to evaluate sowing quality and grain yield of corn intercropped with three forage species of the Urochloa genus associated with two corn population densities. The experiment was conducted at the Sao Paulo State University (UNESP), in Jaboticabal-SP, Brazil. The experimental design was randomized blocks in a 2 x 3 factorial scheme with four replicates. The treatments consisted of two corn densities (55,000 and 75,000 plants ha(-1)) intercropped with three forages (Urochloa brizantha, Urochloa decumbens and Urochloa ruziziensis) sown between rows of corn in the V4 stage. The following corn variables were analysed: mean number of days for emergence, longitudinal distribution, grain yield, initial population and final population. There were differences between corn populations (p < 0.1) and the intercropping of corn with the species U. brizantha and U. ruziziensis promoted the best results, which permitted concluding that the cultivation of corn at the population density of 75,000 plants ha(-1) intercropped U. brizantha and U. ruziziensis promoted better sowing quality and, consequently, higher grain yields.
Keywords: no-tillage system; crop-livestock integration; crop rotation